2020
DOI: 10.1039/d0nr02241a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight in site-selective and anisotropic etching of prussian blue analogues toward designable complex architectures for efficient energy storage

Abstract: Two distinct regions formed inside NCP cubes determine the position and anisotropic pathway of subsequent chemical etching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…proposed that inside NiCo PBA nanocubes, there are two distinct regions. [ 78 ] As the kinetics illustrated in Figure a, the growth of (100) crystal planes leads to six densely stacked cone‐shaped regions while aggregation of primary nanoparticles results in defect‐enriched loose regions. The start position and direction of etching were primarily determined by the loose regions, where unprotected Ni sites were selectively exposed.…”
Section: Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…proposed that inside NiCo PBA nanocubes, there are two distinct regions. [ 78 ] As the kinetics illustrated in Figure a, the growth of (100) crystal planes leads to six densely stacked cone‐shaped regions while aggregation of primary nanoparticles results in defect‐enriched loose regions. The start position and direction of etching were primarily determined by the loose regions, where unprotected Ni sites were selectively exposed.…”
Section: Principlesmentioning
confidence: 99%
“…b) Structure dependent etching mechanism and c-j) the corresponding SEM/TEM images of etched NiCo PBAs in panel (b). Reproduced with permission [78]. Copyright 2020, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24] Nanostructure design is considered a promising strategy for addressing the pulverization issue of TMOs by alleviating structure strains induced by Li + insertion and phase conversion. [25,26] For example, Ni-Co-Mn oxide hollow microspheres, [27] CoFe 2 O 4 multi-shell hollow nanospheres, [28] and hollow Fe 3 O 4 /carbon [29] have been prepared via self-template transformation, calcination, and chemical etching and applied in LIBs as anode materials. [30][31][32] In comparison with their bulk/solid counterparts, these materials respectively exhibited improved capacities and cycling stability.…”
Section: Doi: 101002/adsu202200153mentioning
confidence: 99%
“…In general, the chemical etching process prone to occur on the loose region of crystal which possessed more defects (Nai, Lu, Yu, Wang, & Lou, 2017;Shi et al, 2021;H. Xu et al, 2020;Yu et al, 2016), and as shown in TEM image and XRD pattern, the high crystallization and low defect of PB nanorod slow down the erosion from hydroxyl ions.…”
Section: δG°=δh°−tδs° (10)mentioning
confidence: 99%